Programa de Intervenção Precoce Avançado (PIPA): um estudo à luz dos princípios da promoção da saúde - Almeida, Rosely Oliveira de (2019)
Introduction: Health promotion should include environmental, political, social and other factors that may contribute to the health needs of human beings and promote human development assistance throughout their life span. In the case of newborns at risk, even more attention is necessary when it comes to health care, since prematurity is one of the main causes of death, and is also the cause of sequels that can last until adulthood, such as motor retardation, visual and respiratory conditions, and cognitive deficit, among others. Objective: understand the “Advanced Early Intervention Program” (PIPA, in Portuguese) in the municipality of Patos de Minas, state of Minas Gerais, its actions and its results and how the program, both in its legal resolution and development in the municipality of Patos de Minas encompasses the principles of health promotion outlined in the Ottawa Charter (1986). Method: qualitative, descriptive and documentary study carried out at “The Parents and Friends' Association of Exceptional People” (APAE, in Portuguese), in the municipality of Patos de Minas, Minas Gerais state. Content analysis of PIPA documents (CIB-SUS / MG deliberations, annual reports and other documents with aggregated information) was carried out in light of the principles of Health Promotion outlined in the Ottawa Charter. Results: PIPA both in its resolution and in its development in Patos de Minas does not fully meet the principles of health promotion. With regards to the three prerequisites of health promotion, PIPA in its legal resolution meets the requirements of advocacy and mediation, though only to some extent the requirement of training. In the municipality, it meets the criteria of defense of cause and qualification, but only to a certain extent the criterion of mediation. As to the five fields of action, PIPA in its resolution meets the requirement of implementation of public policies and to some extent the reorientation of health services. Also, in Patos de Minas only two fields are partially satisfied: the implementation of public policies and the creation of healthy environments. Conclusion: in the setting investigated, there is a need to promote the empowerment of users for social inclusion, strengthen community actions, make the program known among the population (highlighting the importance of investing in the prevention of newborns at risk), evaluate and expand the program with the participation of the community, provide health care that breaks away from the clinical model, and develop actions to promote the creation of healthy environments.